2016
DOI: 10.1097/md.0000000000004275
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced functional connectivity alterations in nasopharyngeal carcinoma patients with radiotherapy

Abstract: The study aims to investigate the radiation-induced brain functional alterations in nasopharyngeal carcinoma (NPC) patients who received radiotherapy (RT) using functional magnetic resonance imaging (fMRI) and statistic scale.The fMRI data of 35 NPC patients with RT and 24 demographically matched untreated NPC patients were acquired. Montreal Cognitive Assessment (MoCA) was also measured to evaluate their global cognition performance. Multivariate pattern analysis was performed to find the significantly altere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 46 publications
4
29
0
Order By: Relevance
“…The method of PCA+SVM was quite helpful to improve the accuracy of the classification, and validly detected the abnormal brain regions, which widely contained the previous research achievement. As shown in Table 1, our results were consistent with previous studies, suggesting that the method was in favour of identifying the injury caused by RT [5][6][7]9]. The classification accuracy was 82.5 %, indicating that the method could well identify the abnormal changes induced by RT.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The method of PCA+SVM was quite helpful to improve the accuracy of the classification, and validly detected the abnormal brain regions, which widely contained the previous research achievement. As shown in Table 1, our results were consistent with previous studies, suggesting that the method was in favour of identifying the injury caused by RT [5][6][7]9]. The classification accuracy was 82.5 %, indicating that the method could well identify the abnormal changes induced by RT.…”
Section: Resultssupporting
confidence: 81%
“…Previous studies have found that radiation therapy for NPC resulted in multiple regions abnormalities, such as temporal lobe necrosis [3,4], precuneus, cuneus, lateral occipital cortex [5], the vermis, hippocampus, cerebellum lobule, middle occipital lobe, and insula [6,7]. However, it was difficult for doctors to identify the abnormal changes after radiotherapy (RT) based on original image features.…”
Section: Introductionmentioning
confidence: 99%
“…Diffusion kurtosis imaging (DKI) can detect the early presence of relatively subtle radiation-induced changes before temporal lobe necrosis [25,26]. Altered brain functional connections were significantly correlated to the Montreal Cognitive Assessment scores in NPC patients, which may serve as a potential biomarker of the brain functional impairments [27,28]. Thus, structural and functional MRI were more sensitive than conventional MRI in determining radiation induced brain damage.…”
Section: Discussionmentioning
confidence: 99%
“…Nasopharyngeal carcinoma, after a timely and standardized radical radiotherapy or integrated radiotherapy and chemotherapy, can lead to local and/or regional recurrence in 20–30% of patients. Local nasopharyngeal and skull-based recurrence are the main reasons for the failure of local treatment of NPC after radiotherapy ( 9 11 ). Retrospective studies have shown that salvage therapy can improve survival in patients with a single local recurrence (especially those with local recurrence of T1-2) ( 12 ).…”
Section: Discussionmentioning
confidence: 99%